1996
DOI: 10.1016/s0092-8674(00)80102-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of a DNA Repair Enzyme, 3-Methyladenine DNA Glycosylase II, from Escherichia coli

Abstract: The three-dimensional structure of Escherichia coli 3-methyladenine DNA glycosylase II, which removes numerous alkylated bases from DNA, was solved at 2.3 A resolution. The enzyme consists of three domains: one alpha + beta fold domain with a similarity to one-half of the eukaryotic TATA box-binding protein, and two all alpha-helical domains similar to those of Escherichia coli endonuclease III with combined N-glycosylase/abasic lyase activity. Mutagenesis and model-building studies suggest that the active sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 55 publications
5
127
1
Order By: Relevance
“…Its surface has a prominent cleft lined with electron-rich aromatic residues that may guide an extrahelical, positively charged, alkylated base into a position where it may be subject to nucleophilic attack by water deprotonated by an Asp residue. AlkA is a compact globular protein consisting of 13 α-helices and a five-stranded anti-parallel β-sheet [158,159]. The structure consists of three roughly equal-sized domains (Figure 7).…”
Section: Three-dimensional Structure Of Alkamentioning
confidence: 99%
“…Its surface has a prominent cleft lined with electron-rich aromatic residues that may guide an extrahelical, positively charged, alkylated base into a position where it may be subject to nucleophilic attack by water deprotonated by an Asp residue. AlkA is a compact globular protein consisting of 13 α-helices and a five-stranded anti-parallel β-sheet [158,159]. The structure consists of three roughly equal-sized domains (Figure 7).…”
Section: Three-dimensional Structure Of Alkamentioning
confidence: 99%
“…The 3-D structure of AlkA is available and has clarified the catalytic properties of the enzyme (Labahn et al, 1996;Yamagata et al, 1996). A comprehensive review (Hollis et al, 2000) describes the main structural features of AlkA.…”
Section: Methylating Agentsmentioning
confidence: 99%
“…There are now numerous examples of enzymes that repair or methylate DNA that act via base-flipping mechanisms (34 -36). These include HhaI and HaeIII methyltransferases (37,38), T4 endonuclease V (39,40), uracil DNA glycosylase (41, 42), 3-methyladenine DNA glycosylase II (43,44), and DNA photolyase (45). Several authors have suggested that alkyltransferase follows a similar general mechanism (34,36,46,47), and the crystal structure of the Ada-C protein would be consistent with such a model, in which the methylated base is flipped out of the DNA structure and rotated into a binding pocket in the protein (6,7).…”
Section: Repair Of O 6 -Benzylguaninementioning
confidence: 99%